2014
DOI: 10.1159/000367791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Brachial Cuff-Based Oscillometric Method for Estimating Central Systolic Pressure in Hemodialysis Patients

Abstract: Background/Aims: Elevated wave reflections and arterial stiffness, as well as ambulatory blood pressure (BP) are independent predictors of cardiovascular risk in end-stage-renal-disease. This study is the first to evaluate in hemodialysis patients the validity of a new ambulatory oscillometric device (Mobil-O-Graph, IEM, Germany), which estimates aortic BP, augmentation index (AIx) and pulse wave velocity (PWV). Methods: Aortic SBP (aSBP), heart rate-adjusted AIx (AIx(75)) and PWV measured with Mobil-O-Graph w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 33 publications
0
61
0
9
Order By: Relevance
“…First, Mobil-O-Graph records brachial BP and pulse waves using the oscillometric method; although this differs from the most widely applied technique of applanation tonometry (23), previous validation studies in different populations (including patients with ESRD) showed acceptable agreement between Mobil-O-Graph-derived variables and invasive and noninvasive measurements (23,24,28,30,31). Second, because this was a pilot study, no power estimation was performed before its initiation; we believe, however, that the number of participants, together with the high number of readings (.120) during the 48-hour recordings, provided adequate power.…”
Section: Discussionmentioning
confidence: 99%
“…First, Mobil-O-Graph records brachial BP and pulse waves using the oscillometric method; although this differs from the most widely applied technique of applanation tonometry (23), previous validation studies in different populations (including patients with ESRD) showed acceptable agreement between Mobil-O-Graph-derived variables and invasive and noninvasive measurements (23,24,28,30,31). Second, because this was a pilot study, no power estimation was performed before its initiation; we believe, however, that the number of participants, together with the high number of readings (.120) during the 48-hour recordings, provided adequate power.…”
Section: Discussionmentioning
confidence: 99%
“…The device uses the integrated ARCSolver algorithms (Austrian Institute of Technology, Vienna, Austria) to derive aortic stiffness surrogates based on brachial BP readings by a generalized transfer function [31,32]. Previous studies have proven the validity of the Mobil-O-Graph for BP monitoring and pulse wave analysis against established invasive and noninvasive techniques in various populations, including hemodialysis patients [23,[32][33][34][35]. The measurements were taken of the non-fistula arm with circumference-adapted arm cuffs and started before the midweek dialysis session independent of the dialysis shift.…”
Section: Data Collection and Measurementsmentioning
confidence: 99%
“…20,[22][23][24] In hemodialysis patients, Mobil-O-Graph provided comparable estimates of office aortic SBP, AIx, and PWV with that obtained by Sphygmocor (ArtCor, Sydney, Australia), which is the most widely applied method for noninvasive assessment of these parameters. 14 …”
Section: Study Procedures and Ambulatory Bp Monitoringmentioning
confidence: 99%
“…13 However, PWV displayed only a minimal increase over time that reached again statistical significance at the end of the 3-day interval. 13 All devices measuring arterial stiffness and central BP indexes use brachial BP for calibration of the aortic waveforms 14 ; such measurements are subject to errors inserted by predialysis or postdialysis office BP readings, which are known to be highly inaccurate and poorly reflect the true BP load due to numerous factors, such as the white-coat effect, patient frustration to start dialysis and leave the unit quickly, anxiety for correct arteriovenous fistula needling, and truly high BP variability during the intra-and interdialytic periods. 11 We have, therefore hypothesized that ambulatory estimates of arterial stiffness and central BP parameters may have stronger associations with cardiovascular events and mortality in this population.…”
mentioning
confidence: 99%